Nevşehir 1913 Salnamesi (Politics, 2021)
Yearbooks are the books that play an important role in increasing the social and cultural level of the Greek community in the provinces of the Ottoman society and are published annually. Its content usually includes social events, science, medicine, geography, history, interesting articles, useful information, anecdotes, stories, proverbs and religious texts with advices. This yearbook has been prepared as a resource for researchers studying the Karamanli language and the history of Nevşehir. The works written in Karamanli language are generally of religious content, though few in number. Therefore most valuable works to be examined to understand the social life of the period are yearbooks, due to such quality. This book, being the first of the two yearbooks issued for Nevşehir, has been prepared for the Turkish speaking Greek community living in Anatolia, in order to enable them to obtain information on the present, past and future, to keep the customs and traditions alive and to present general information. This work, prepared and compiled in 1912 and presented to its readers in 1913, has been translated into modern Turkish and submitted to all researchers, academicians and readers.